Ускоритель электронов с многоапертурным плазменным эмиттером; Известия вузов. Физика; Т. 57, № 11-3 - Воробьёв М. С. Максим Сергеевич; Коваль Н. Н. Николай Николаевич; Сулакшин С. А.; Шугуров В. В. Владимир Викторович (2014, 2014)
Заглавие с экрана